A critical role for the fascin family of actin bundling proteins in axon development, brain wiring and function. - Hardin, K.R.; Penas, A.B.; Joubert, S.; Ye, C.; Myers, K.R.; Zheng, J.Q. (Molecular and Cellular Neurosciences, 2025)
Actin-based cell motility drives many neurodevelopmental events including guided axonal growth. Fascin is a major family of F-actin bundling proteins, but its role in axon development in vivo and brain wiring remains unclear. Here, we report that fascin is required for axon development, brain wiring and function. We show that fascin is enriched in the motile filopodia of axonal growth cones and its inhibition impairs axonal extension and branching of hippocampal neurons in culture. We next provide evidence that fascin is essential for axon development and brain wiring in vivo using Drosophila melanogaster as a model. Drosophila expresses a single ortholog of mammalian fascin called Singed (Sn), which is expressed in the mushroom body (MB) of the central nervous system. Loss of Sn causes severe MB disruption, marked by ?- and ?-lobe defects indicative of altered axonal guidance. Sn-null flies also exhibit defective sensorimotor behaviors as assessed by the negative geotaxis assay. MB-specific expression of Sn in Sn-null flies rescues MB structure and sensorimotor deficits, indicating that Sn functions autonomously in MB neurons. Together, our data from primary neuronal culture and in vivo models highlight a critical role for fascin in brain development and function.